Effect of coal bottom ash & binder addition into CaO-based Sorbent on CO2capture performance - Mohamed, M. (Italian Association of Chemical Engineering - AIDIC, 2017)
CO2 capture through series of calcination and carbonation cycle using natural solid CaO-based sorbent has been an emerging and promising technologies due to economic and environment advantages. However natural solid sorbent experiences rapid degradation in capture capacity as increasing reaction cycles. This paper described the derivation of CaO-based sorbent from cockle shell (CS) with the addition of coal bottom ash (CBA) and several type of binders as a mean to increase sorbent cyclic-stability. Cockle shell was mixed with coal bottom ash and binders at percentage weight ratio of 85:10:5 while the examined binders were aluminum pillared clay (Montmorillonite), magnesium oxide (MgO) and kaolinite. Series of calcination and carbonation was demonstrated via thermal-gravimetric analyzer (TGA EXSTAR 6300 Series). Calcination was performed at 850 °C in pure N2 environment (100 mL/min) to synthesize CaO from the cockle shell while carbonation was conducted in pure CO2 environment (50 mL/min) at 650 °C. The study found that CaO conversion of fresh sorbents was reduced by 15 once CS was added with CBA and binders. CS with CBA and Montmorillonite displayed the highest CaO conversion during the second regeneration cycle onwards while the lowest conversion was observed from derived-sorbent of CS with CBA and MgO. Fresh sorbent of CS obtained the highest CO2 capacity which was 0.52 gCO2/gsorbent while the capture capacity of other fresh sorbents was within 0.46-0.49 gCO2/gsorbent. Derived sorbent from CS with CBA and Montmorillonite exhibited the highest capture capacity once it was reused at all reaction cycles. CS-free additive and CS with CBA and MgO illustrated the highest loss in CO2 capture capacity within all cycles which indicate that suitable binders have increased the performance of the derived natural-sorbents. Copyright © 2017, AIDIC Servizi S.r.l..